Diversity and Potential of Local Actinobacteria from Bedengan Forest for Sustainable Antibiotic Solutions - Sakaroni, Rubiyatna; Azizah, Isnaniar Rahmatul (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
Natural antibiotics may offer a solution to the growing issue of pathogenic bacterial resistance caused by the widespread use of synthetic antibiotics. This study investigates the diversity and potential of Actinobacteria from the rhizosphere of Pinus in the Selorejo Bedengan Forest, Malang City, which has been exposed to synthetic agricultural chemicals for an extended period. Soil samples were collected and analyzed for various environmental factors, including pH, moisture, organic matter, and light intensity. A total of seven Actinobacteria isolates were identified, belonging to the genera Streptomyces and Nocardia. The diversity of these isolates was assessed using the Shannon-Wiener index, yielding a moderate diversity value (H' = 2.74). Antibacterial activity was tested against Escherichia coli and Shigella dysenteriae using the pitting method. The results indicated that isolates AC5 and AC7 exhibited inhibition zones of ≥11 mm and ≥12 mm, respectively, categorizing them as having strong antibacterial activity. These findings highlight the significant potential of local Actinobacteria as candidates for the production of natural antibacterial compounds to combat pathogenic bacteria. This research not only supports the development of more environmentally friendly antibiotic alternatives but also encourages the sustainable use of local microbial resources.